Pembinaan Disiplin Siswa oleh Guru di SMK Negeri se-Kecamatan Padang Timur - Fikriyah Afdol; Adi, Nelfia (Global Action and Education for Society, 2023)
This research was motivated by the problems found in Student Discipline Development by Teachers at State Vocational Schools in the East Padang District. This study aims to gather information about Student Discipline Guidance by Teachers in State Vocational Schools throughout the East Padang District in terms of exemplary, supervision, sanctions/punishments, and habituation aspects. This type of research is descriptive quantitative. The research population was students at State Vocational Schools in the East Padang District, totaling 961 people. A sample of 104 people was taken using a proportional stratified random sampling technique. The data collection instrument was a Likert scale model questionnaire with five answer choices, namely always (SL), often (SR), rarely (JR), sometimes (KD), never (TP). This research questionnaire was tested on 30 people outside the sample in the population and processed using the SPSS 26 program, the results of the instrument were declared valid and reliable. Furthermore, the data is processed by the average formula (mean). The results showed that the teacher's fostering of student discipline in aspects 1) exemplary with an average score of 4.15 is in the good category, 2) supervision with an average score of 3.68 is in the pretty good category, 3) sanctions/punishments with an average score of 3.98 are in the good category, 4) habituation with an average score of 4.21 is in the good category. Thus it can be concluded that Student Discipline Development by Teachers in State Vocational Schools throughout the East Padang District is in the good category with an average score of 4.01. Based on these results, the author suggests that the Guidance of Student Discipline by Teachers in State Vocational Schools in the East Padang District be maintained and needs to be further improved so as to improve the effective coaching of student discipline by teachers.